Δ15N of Nitric Oxide Produced Under Aerobic or Anaerobic Conditions From Seven Soils and Their Associated N Isotope Fractionations. Issue 9 (15th September 2020) - Su, Chenxia; Kang, Ronghua; Zhu, Weixing; Huang, Wentao; Song, Linlin; Wang, Ang; Liu, Dongwei; Quan, Zhi; Zhu, Feifei; Fu, Pingqing; Fang, Yunting
Abstract: Measuring the nitrogen isotope compositions (δ 15 N) of nitric oxide (NO) from different sources helps to quantify the relative contributions of atmospheric NOx . Soil is one of the most important sources of atmospheric NOx, but only limited measurements on the δ 15 N of soil‐emitted NO exist, hampering our ability to partition sources to air pollution. Here we conducted soil incubations to measure the δ 15 N‐NO under defined aerobic or anaerobic conditions, favoring either nitrification or denitrification. Soils were collected from seven sites spanning three ecosystems in northern China (two agricultural, two forest, and three grassland sites). We found that the δ 15 N‐NO and their associated N isotope fractionations were significantly different between anaerobic and aerobic conditions in seven soils. Under aerobic condition, the δ 15 N‐NO ranged from −62‰ to −50‰ (averaged −56 ± 4‰), being significantly more negative (by 23‰) than those under anaerobic condition (−45‰ to −23‰, averaged −33 ± 7‰). The apparent N isotope fractionation for NO production under aerobic condition ( 15 ε aerobic = 61 ± 3‰) was significantly higher (by 26‰) than under anaerobic condition ( 15 ε anaerobic = 35 ± 6‰), with a small variability among ecosystem types. Our study demonstrates that the δ 15 N‐NO from different soils are very different from fuel combustions (mainly from 0‰ to +20‰), supporting that measuring 15 N is a useful tool to partition the contributions of soil NO to atmospheric NOx . Our results also imply δ 15 N‐NO produced by nitrification and denitrification distinctly different, as these two processes are dominant processes producing NO under aerobic and anaerobic conditions, respectively. Plain Language Summary: Nitric oxide (NO) affects the atmosphere chemistry and NO itself a key component of air pollution and a precursor to other air pollutants like particulate matter and ozone. To reduce the air pollution, it is crucial to identify the atmospheric NO sources. Measuring 15 N natural abundance has been considered as a promising tool to identify different sources, but the measurement on δ 15 N for soil‐emitted NO is limited, adding to the large uncertainties on NO partitioning. Here we measured the δ 15 N‐NO emitted from three ecosystem types across seven sites (two agriculture, two forest, and three grassland sites) under defined anaerobic or aerobic conditions. We found that soil‐emitted NO was 15 N‐depleted (−62‰ to −23‰) related to the source from fossil fuel combustion (0–20‰), suggesting that δ 15 N can be used to separate these two sources. We also found that the δ 15 N‐NO under aerobic condition (nitrification prevailing, −62‰ to −50‰) was much lower than under anaerobic condition (denitrification prevailing, −45‰ to −23‰), which provide a useful tool to better understand the relative contributions of different sources of NO. In sum, soil‐emitted NO has their own different isotope fingerprint, depending on the soil oxygen conditions, and can be used to partition sources. Key Points: The δ 15 N‐NO from soil (−62‰ to −23‰) is different from fuel combustion (0‰ to 20‰), allowing effective source partition The δ 15 N‐NO produced under aerobic condition (favor nitrification) was more negative than under anaerobic condition (favor denitrification) The 15 ε for NO production under aerobic condition (61 ± 3‰) was significantly higher than under anaerobic condition (35 ± 6‰)